Woman between Two Kingdoms - Castro-Woodhouse, Leslie (Cornell University Press, 2021)
"Woman Between Two Kingdoms explores the story of Dara Rasami, one of 153 wives of King Chulalongkorn of Siam in Thailand during the late nineteenth and early twentieth centuries. Born in a kingdom near Siam called Lan Na, Dara served as both hostage and diplomat for her family and nation. Thought of as a ""harem"" by the West, Siam's Inner Palace actually formed a nexus between the domestic and the political. Dara's role as an ethnic ""other"" among the royal concubines assisted the Siamese in both consolidating the kingdom's territory and building a local version of Europe's hierarchy of civilizations. Dara Rasami's story provides a fresh perspective on both the socio-political roles played by Siamese palace women, and how Siam responded to the intense imperialist pressures it faced in the late nineteenth century."